Methods for Lithium Ion NASICON Preparation: From Solid-State Synthesis to Highly Conductive Glass-Ceramics - Dias, Jeferson A. [UNESP]; Santagneli, Silvia H. [UNESP]; Messaddeq, Younès [UNESP] (American Chemical Society (ACS), 2020)
Lithium ion-containing Na+ Super Ionic Conductor (NASICON) electrolytes are important materials for new energy-storage technologies. The NASICON abbreviation represents several compounds with similar structures applied as solid electrolytes, including those conductors of lithium ions. Different methods have been used to synthesize these materials, as well as innumerous other methods used to form the electrolyte in its final shape. The synthesis methods and processing techniques significantly affect the microstructure and conductivity of the electrolyte as a result. Therefore, this paper provides an overview of the main synthesis methods and processing techniques applied for lithium ion NASICON production. First, a general view of the NASICON structure and the variety of possible compositions will be discussed. Next, the influence of the synthesis methods (e.g., solid-state reaction, sol-gel, polymeric precursor, sol-gel/electrospinning) and sintering techniques (e.g., conventional, microwave, and Spark Plasma Sintering) will be presented. A special topic will be devoted for glass-ceramics production and evaluation, based on their advantageous ionic conductivity and potentiality for practical use on a large-scale. Moreover, the current results for electrochemical cells simulating the application of these materials in batteries will be presented. Finally, a general point of view of the authors about the future for NASICON electrolytes will be provided, presenting oncoming trends for research.